THE INNOCENT CARBIMAZOLE - Cheng, Wee Mee; Kuan, Yueh Chien; Lai, Qi Ji; Akbar, Sharifah Aishah bt Wan Mohamad (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Agranulocytosis is a life-threatening condition with mortality rate of 21.5% seen in 0.30.6% of patients taking thionamides. However, thionamides may not be the only culprit and other aetiologies should be considered. CASE We describe here a 29-year-old male with Grave’s disease diagnosed since 2017 who was recently restarted on high dose carbimazole after a period of non-adherence leading to raised Free T4 53.7 pmol/L [13.1 - 21.3] with suppressed TSH. He presented with fever, sore throat, and malaise. Blood investigations revealed leukopenia with agranulocytosis and thrombocytopenia - total white cells of 1.81 x 103/ul, neutrophil count of 0.65 x 103/ul and platelet of 110 x 103/ul. Renal and liver profile were normal, but his lactate dehydrogenase was elevated at 716 U/L [135 - 225]. He was admitted with the initial suspicion of carbimazoleinduced agranulocytosis. Hence, carbimazole was withheld and treatment with cholestyramine 16 g/day, broad spectrum antibiotics and subcutaneous Neupogen were commenced. Oral lithium was later added but he developed generalized maculopapular rash. However, as physical examination revealed generalised lymphadenopathy, other differential diagnoses were also pursued. Finally histopathological examination of the excisional biopsy of the right inguinal lymph node showed necrotising histiocytic lymphadenitis consistent with Kikuchi-Fujimoto disease. Anti-nuclear antibody was negative and complements levels were normal. The rheumatology team initiated oral prednisolone and this was followed by prompt recovery of blood counts (total white cells 9.29 x 103/ul, neutrophil 3.39 x 103/ul and platelet 196 x 103/ul) a week later. He was restarted on carbimazole to render him euthyroid before definitive thyroidectomy. Conclusion This case describes a rare case of Kikuchi-Fujimoto disease and highlights the importance of considering and pursuing other aetiologies of agranulocytosis especially in a patient who has been on and off carbimazole for years.